E-COMMERCE CONSUMER BEHAVIOR TRANSFORMATION IN POST-PANDEMIC INDONESIA - Zaenal Aripin; Fitriana; Farida Yulianty (PT. Kreatif Indonesia Satu, 2024)
Background: The COVID-19 pandemic accelerated Indonesian e-commerce adoption by 3-5 years, fundamentally altering consumer shopping behaviors, channel preferences, and purchase decision processes. Questions remain regarding behavioral persistence post-pandemic and underlying factors sustaining digital commerce engagement. Aims: This research investigates post-pandemic e-commerce consumer behavior transformation examining persistent behavioral changes, psychological and functional drivers sustaining adoption, and consumer segmentation patterns based on digital literacy and shopping orientations. Research Method: A mixed-methods design combined survey analysis of 342 consumers with 18 in-depth interviews. Statistical analysis utilized paired t-tests for behavioral changes and cluster analysis for segmentation. Results and Conclusion: Findings reveal 67% increase in purchase frequency, 58% category expansion, and 72% preference for online channels versus pre-pandemic baselines. Trust (β=0.44), convenience (β=0.39), and value perception (β=0.36) emerge as primary drivers. Four distinct segments identified: Digital Natives (28%), Pragmatic Adopters (35%), Hesitant Users (24%), Traditional Preferrers (13%). Contribution: This study extends consumer behavior literature by empirically documenting pandemic-accelerated digital transformation persistence and identifying psychological mechanisms sustaining adoption. The segmentation framework provides practical guidance for targeted marketing strategies.